THYROTOXIC PERIODIC PARALYSIS - Haider, Miqdad; Chachar, Aijaz Zeeshan Khan; Munir, Atif (Journal of Ayub Medical College Abbottabad, 2019)
Thyrotoxic periodic paralysis is an uncommon disorder characterized by hypokalaemia, thyrotoxicosis and paralysis, most commonly seen in South Asian males. Aim of our case series is to highlight the significance of this reversible cause of patients presenting with neuromuscular paralysis. We present case series of 1 Asian and three Caucasian patients with thyrotoxic periodic paralysis who came with neuromuscular weakness secondary to thyrotoxicosis. All made a swift and uneventful recovery with no recurrence. Thyrotoxic periodic paralysis (TPP) is an infrequent condition having recurrent episodes of muscle weakness as main feature. Hypokalaemia is a common finding seen in these patients. Resolution of the attacks is achieved with correction of hypokalaemia and hyperthyroidism. Keywords: Hyperthyroidism; Thyrotoxic periodic paralysis; Hypokalaemia; Paraparesis